Dental Caries And Its Correlation With Nutritional Status Among Children From 3 To18 Year-Old - Alsayegh, Homood Mohammed; S Alwadai, Naif mohsen; maroof, Faisal ALI; Fadelelahy, Moaaz Alem; AlGhamdi, Basem Saad; Darwish, Hassan Ahmed; Alharbi, Afaf Hamid; ALluqmani, Budoor Mulfi; Alessa, Nada Atif; Althobaiti, Malak Abdulmajeed; Alsulami, Musab Abdullah (Migration Letters, 2022)
Background: Globally, dental caries appears a major public health problem and a widespread non -communicable disease. It is more prevalent among children. A combination of poor oral health status and malnourishment ultimately affect the quality of life of the person. Aim: This study aimed to examine the prevalence of dental caries and its correlation with nutritional status in 3–18-year olds. Methods: The cross-sectional study was conducted among 3–18-year olds at dental clinics from January to July 2022 in KSA. A total of 859 subjects participated in the study. The body mass index (BMI) was used to assess the nutritional status of participants. The anthropometric measurements for BMI were recorded. The World Health Organization (WHO) Child Growth Standards Reference for BMI was used to categorize the participants into obese/overweight, normal, or underweight for age. Dental caries was assessed using decayed, missing, and filled primary teeth (DMFT) and decayed extracted filled teeth (deft) index. A parent-administered questionnaire was used to obtain data on oral hygiene practice, parental education, dental visits, and sugar exposure. Results: The prevalence of dental caries was found to be 48.8%. A total of 54.6% of study participants were malnourished, and 47.7 % were underweight for their age. The nutritional status was found to be inversely related to dental caries. The children with higher B[1]MI (obese and overweight) were likely to have less caries experience. Conclusion: Nutritional status was found to be inversely related to dental caries. Children with lesser BMI were at higher risk of having dental caries and vice versa. Clinical significance: Dental caries and nutritional status have common risk factors. Diet is the major risk factor, common to both conditions. Diet is a modifiable risk factor. Therefore, strategies can be developed and targeted at the prevention of both dental caries, and malnutrition in the community. Healthy dietary habits and practices can be promoted for the control of dental caries and malnutrition.